Outcomes after the Ross procedure with pulmonary autograft reinforcement by reimplantationCentral MessagePerspective - Lisa Guirgis, MD; Sébastien Hascoet, MD, PhD; Isabelle Van Aerschot, MD; Jelena Radojevic, MD; Mohamed Ly, MD; Sarah Cohen, MD, PhD; Emre Belli, MD (JTCVS Techniques)
Background: Pulmonary autograft reinforcement to prevent dilatation and subsequent neo-aortic valve regurgitation has been reported; however, data on long-term function of the neo-aortic valve after this modified Ross procedure are lacking. Our objective here was to assess long-term outcomes of the modified Ross procedure with autograft reinforcement using the reimplantation technique. Patients: The outcomes of 61 consecutive patients managed using the Dacron-conduit reinforced Ross procedure between 2009 and 2021 were reviewed. Most patients had a unicuspid or bicuspid aortic valve (n = 52; 85%), predominant aortic valve regurgitation (n = 42; 77%), and >30 mm dilatation of the ascending aorta (n = 33; 54%). A prior aortic valve procedure was noted in 47 patients (77%) patients, including 38 (62%) with surgical repair and 9 (15%) with balloon dilatation. The pulmonary autograft was reimplanted within a Dacron conduit with a median diameter of 25.6 mm (range, 20-30 mm) using the David valve-sparing aortic root replacement technique. Results: All patients survived. The median age at surgery was 16.8 years (range, 6-38 years). Neo-aortic valve replacement was required in 3 patients (4.9%; 95% CI, 0.34%- 12.7%) because of infective endocarditis, left ventricular false aneurysm, and leaflet perforation, respectively; the repeat procedure was done early in 2 of these patients (2 of 61; 3%). Six patients required right ventricular outflow conduit replacement, 5 by surgery and 1 percutaneously. The median duration of follow-up was 90 months (range, 10-124 months). The 5- and 10-year rates of reintervention-free survival were 84.3% (95% CI, 74%-95%) and 81.6% (95% CI, 72%-93%), respectively, and 5-year survival without aortic reintervention was 94.5% (95% CI, 88%-100%), with little change at 10 years. No patients experienced deterioration of initial neo-aortic valve function (ie, regurgitation or stenosis). Conclusions: Autograft reinforcement using the reimplantation technique allowed expansion of Ross procedure indications to all patients requiring aortic valve replacement and prevented neo-aortic root dilatation. Failures were uncommon. Long-term follow-up data showed stable neo-aortic valve function.